2018
DOI: 10.1186/s12870-018-1440-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite profiling and transcriptomic analyses reveal an essential role of UVR8-mediated signal transduction pathway in regulating flavonoid biosynthesis in tea plants (Camellia sinensis) in response to shading

Abstract: BackgroundTea is the most popular nonalcoholic beverage worldwide for its pleasant characteristics and healthful properties. Catechins, theanine and caffeine are the major natural products in tea buds and leaves that determine tea qualities such as infusion colors, tastes and fragrances, as well as their health benefits. Shading is a traditional and effective practice to modify natural product accumulation and to enhance the tea quality in tea plantation. However, the mechanism underlying the shading effects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 68 publications
(142 reference statements)
6
90
0
1
Order By: Relevance
“…For example, only EGCG was induced, while the abundance of other catechins remains unchanged. In addition, the genes (UVR-8, COP1, HY5) in the UV-B signaling transduction module are not consistently UV-B up-regulated (Liu L. et al, 2018) as found in many other plant species (Rizzini et al, 2011;Jenkins, 2017).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…For example, only EGCG was induced, while the abundance of other catechins remains unchanged. In addition, the genes (UVR-8, COP1, HY5) in the UV-B signaling transduction module are not consistently UV-B up-regulated (Liu L. et al, 2018) as found in many other plant species (Rizzini et al, 2011;Jenkins, 2017).…”
Section: Introductionmentioning
confidence: 80%
“…Interestingly, the UV-B induced changes in the tested catechins in both cultivars are related to their original catechin abundances: the higher original catechin abundances in tea leaves, the less increase of UV-B induced catechin production after the first 30 min treatment and the more significant decrease of the UV-B induced catechin production after 360 min treatment. Besides, a recently published study indicated that long periods (1 to 16 days, 8 h per day) of a mild UV-B treatment (20 µW/cm 2 ) applied to tea plants did not affect the abundance of the majority of flavonoid compounds, except for that of EGCG, kaempferol-7-O-glucoside, and GC (Liu L. et al, 2018). However, the detected GC enhancement only after 16 days of UV-B treatment relative to the control plants grown in hydroponic culture might result from a substantial decrease in all tested metabolites in control, not from UV-B treatment.…”
Section: Uv-b Induced Changes In Flavonoid Biosynthesis Pathwaymentioning
confidence: 95%
See 1 more Smart Citation
“…In this traditional cultivation method, tea trees are covered with shading nets when new shoots emerge, and they are grown under the shade before being harvested after between 14 and 30 days. During this period, the contents of chlorophylls (Chls) and free amino acids including theanine are increased, and that of catechins is decreased, in the tea shoot [6][7][8][9][10][11]. Tea trees usually produce new shoots thrice in a year from spring to fall in Japanese tea plantations.…”
Section: Introductionmentioning
confidence: 99%
“…In conventional tea plants, flavonoid metabolism is enhanced under strong light, but the opposite results are observed in light-sensitive tea plants 19 . Catechins are usually decreased in green-leaf tea plants with shading treatment due to an alternation in the transcription level of the genes responsible for catechin biosynthesis 43 . In the present study, tea plants were grown in the same surroundings.…”
Section: Discussionmentioning
confidence: 99%